SISTEM INFORMASI BANK SAMPAH SUKOREJO BERBASIS CLIENT SERVER - Lukman Fakih Lidimilah; Hermanto (Department of Science and Technology Ibrahimy University, 2018)
Services to customers that have not been optimal with the implementation of the note-taking model, recording and making reports to the leadership that are still often a complaint for officers is the forerunner to this research. To overcome the problem that was complained about, then carried out steps that could help facilitate the service in the garbage bank. The solution offered is with the Client Server Design of Sukorejo Refuse Bank Application, so that services to customers can be done effectively and efficiently and can report quickly enough. With the service model that has been assisted by the application of the refuse bank, it is expected that it can also help improve the performance of officers. So that the process of designing this system is more directed, then the system development model is used with the waterfall method. The use of this method is chosen based on the consideration of the scope of application that only interacts within the internal Sukorejo refuse bank itself, therefore it is chosen because the scope of the application is still small scale. This system will be built with the Client Server by considering that one computer unit is reserved for the server and the other can be used as a workstation or client. This application will be created using Visual Basic 2010 and the MySQL database. With this system, it can reduce the problems in the refuse bank, so that the garbage bank can provide better service.